Pengenalan Alat Musik Tradisional Gorontalo (Polopalo) Berbasis Android - Sigit Ramadhan Muda; Yasin Aril Mustofa (Teknik Informatika Fakultas Ilmu Komputer Universitas Ichsan Gorontalo, 2022)
Abstract Polopalo is an idiophone type musical instrument, which is a group of musical instruments whose sound source comes from the body of the instrument itself. The sound that comes out of the polopalo instrument when it is hit or hit, which is caused by vibrations found in the entire Polopalo instrument. Gorontalo traditional musical instrument (polopalo) on an Android-based smartphone. In this way, the process of introducing traditional musical instruments to Gorontalo (Polopalo). The results showed that the introduction of the Gorontalo (polopalo) traditional musical instrument based on Android had fulfilled the programming logic requirements, where CC = V(G) = 8 based on White Box testing, then the system was free from various component errors based on Black Box testing. Thus, the Gorontalo (Polopalo) Android Traditional Musical Instrument Recognition Application was obtained which was reliable and effective so that it could be implemented. Keywords: Traditional musical instruments, Polopalo, Android